Effects of the Early Prevention Program "Keiner FÄllt Durchs Netz" ("Nobody Slips Through the Net") on Child, Mother, and Their Relationship: A Controlled Study. Issue 1 (9th January 2013) - Sidor, Anna; Kunz, Elisabeth; Eickhorst, Andreas; Cierpka, Manfred
ABSTRACT The study investigated the effects of a German family‐supporting prevention program "Keiner fällt durchs Netz" (KfdN; "Nobody Slips Through the Net") after the child's first year in the sample of 152 psychosocially stressed mothers and children who took part in this program and 150 mothers and children from comparison‐group families. The improved level of development posited in the children after intervention as compared to children from the comparison group was confirmed in the social development area (d = .35). In addition, mothers in the KfdN group judged their 1‐year‐old children to be less "difficult" compared to the assessments of the mothers in the comparison group (d = .24). Due to the intervention, the dysfunctionality of the mother–child interaction was reduced (mothers' self‐assessment, d = .27). No intervention effects were found in for degree of maternal stress. The expected intervention effects in maternal sensitivity were not empirically confirmed. The results suggest that the KfdN intervention exerted a direct positive influence on childhood traits such as social development and temperamental "difficulty" and also positively influenced the mothers' perceptions or attitudes toward their children's conduct.